Use of HEC-HMS in floodwave propagation simulations - Bueno, Jorge (2020)
A delicate feature of the flood propagation simulation performed by the program HEC-1 with theoption of the modified Puls method with normal flow approximation is constituted by the estimationof the quanta parameter NSTPS. While it is recognized to be a parameter that one should calibrate, itis usually recommended that it be estimated as the ratio (wave travel time/integration time step). Inthis paper it is shown that numerical experiments conducted with the program FEQ, retained asstandards, when compared with HEC-1 solution, do not confirm the above estimate. The preliminaryresults presented here suggest that the ratio (time to peak of outflow hydrograph/time to peak ofinflow hydrograph) may be a more meaningful, but strongly event dependent,parameter.